2018
DOI: 10.1136/jech-2017-209954
|View full text |Cite
|
Sign up to set email alerts
|

Has the UK Healthy Start voucher scheme been associated with an increased fruit and vegetable intake among target families? Analysis of Health Survey for England data, 2001–2014

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 20 publications
0
13
0
1
Order By: Relevance
“…Griffith et al [ 18 ] used a difference-in-differences analysis of household purchase data 2 years before and after programme implementation, reporting a £2.43/month (£0.61/week) increase in FV spending in Healthy Start eligible households compared to ineligible low-income households with a child aged 4–8 years. Scantlebury et al [ 17 ] compared FV intake among adults and children aged 5 years or over from Healthy Start eligible and ineligible households in England, but reported no association between Healthy Start eligibility and individual FV intake following programme introduction. The present finding adds to the current evidence base, indicating that it is unlikely that Healthy Start vouchers had a discernible impact on the dietary behaviours of its target population, for the study period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Griffith et al [ 18 ] used a difference-in-differences analysis of household purchase data 2 years before and after programme implementation, reporting a £2.43/month (£0.61/week) increase in FV spending in Healthy Start eligible households compared to ineligible low-income households with a child aged 4–8 years. Scantlebury et al [ 17 ] compared FV intake among adults and children aged 5 years or over from Healthy Start eligible and ineligible households in England, but reported no association between Healthy Start eligibility and individual FV intake following programme introduction. The present finding adds to the current evidence base, indicating that it is unlikely that Healthy Start vouchers had a discernible impact on the dietary behaviours of its target population, for the study period.…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative evaluations have found that Healthy Start vouchers were valued by recipients and helped reduce the experience of food insecurity [ 13 , 14 , 16 ]. However, the only two existing large-scale quantitative evaluations of Healthy Start are in contradiction; reporting a null effect on FV intake [ 17 ] and positive effect on FV purchasing [ 18 ], respectively. These two previous evaluations used eligibility, not participation, as the exposure variable.…”
Section: Introductionmentioning
confidence: 99%
“…Griffith et al(11) used a difference-in-differences analysis of household purchase data two years before and after programme implementation, reporting a £2.43/month (£0.61/week) increase in FV spending in Healthy Start eligible households compared to ineligible low-income households with a child aged 4-8 years. Scantlebury et al(10) compared FV intake among adults and children aged 5 years or over from Healthy Start eligible and ineligible households in England, but reported no association between Healthy Start eligibility and individual FV intake following programme introduction. The present finding adds to the current evidence base, indicating that it is unlikely that Healthy Start vouchers had a discernible impact on the dietary behaviours of its target population.…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative evaluations have found that Healthy Start vouchers were valued by recipients and helped reduce the impact of food insecurity(9). However, the only two existing large-scale quantitative evaluations of Healthy Start are in contradiction; reporting a null effect on FV intake(10) and positive effect on FV purchasing(11), respectively. These two previous evaluations used eligibility, not participation, as the exposure variable.…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D supplementation and vitamin D food fortification products are useful to combat vitamin D deficiency at any age [ 14 ]. The UK started the “Healthy Start” program in 2006 to provide free vitamin D supplementation vouchers to low-income pregnant women and children to combat vitamin D deficiency [ 15 ]. In Turkey, the “vitamin D prophylaxis augmentation program” started in 2005 to combat vitamin D deficiency in infants.…”
Section: Introductionmentioning
confidence: 99%